Electronic Structure and Redox of the Antidepressants Venlafaxine and Desvenlafaxine - Jhon Kennedy Alves Pereira (22681627) (2025)
Venlafaxine and its primary metabolite desvenlafaxine are antidepressants that block presynaptic reuptake of serotonin and norepinephrine in the brain. Electroanalytical and computational analyses were performed to evaluate the electrochemical characterization of these drugs through measurements using a carbon paste electrode alongside quantum calculations (DFT and TD–DFT) to support the electrochemical data and propose potential oxidation pathways. The results showed that both venlafaxine and desvenlafaxine exhibit different pH-dependent electrochemical behaviors, with desvenlafaxine showing higher anodic peak intensities at neutral pH, while venlafaxine peaks at alkaline pH. Computational insights from DFT calculations provided a deeper understanding of the molecular charge distribution, orbital profiles, and energetics of both drugs in neutral and protonated states. The Gibbs free energy variations in different medium environments revealed the critical role of the medium in modulating the thermodynamic stability. These findings presented here improve our understanding of the electrochemical and electronic properties of these antidepressants and may pave the way for the development of more effective therapeutic agents.